Pemetaan Potensi Likuifaksi Di Ibu Kota Sofifi, Maluku Utara Berdasarkan Data Muka Air tanah Sebagai Mitigasi Bencana - Armanto Arif; Adi Susilo; Rahim Achmad (Postgraduate, University of Mataram, 2026)
North Maluku Province, an eastern Indonesian region characterized by complex geological features, has its capital city, Sofifi, experiencing rapid development. However, Sofifi is a low-lying area with productive aquifers situated in an active seismic zone, rendering it highly susceptible to liquefaction. Liquefaction, defined as the loss of soil shear strength due to increased pore water pressure during an earthquake, frequently occurs in water-saturated sediments with fine to medium grain sizes. This study assesses liquefaction potential by correlating residual gravity anomalies, groundwater levels, and liquefaction vulnerability maps. Gravity data were sourced from GGMplus satellite imagery (200-meter resolution), and groundwater levels were directly measured at 367 well locations. Spatial analysis, conducted using ArcGIS 18.0 software, generated maps of gravity anomaly distribution and groundwater levels. These maps were subsequently validated against liquefaction susceptibility maps from BNPB (inaRISK). The results indicate a strong correlation between zones of low gravity anomalies (−1.7 to −0.1 mGal) and shallow groundwater levels (0−366 cm) in Sofifi City with high liquefaction vulnerability, particularly in the northwestern and central areas. The integration of geophysical and hydrogeological parameters proved effective in identifying liquefaction-prone zones. These findings are anticipated to serve as a crucial basis for spatial planning and disaster mitigation strategies in coastal urban areas like Sofifi.